A Study of Online Purchase Intention Among Gen X in Malaysia - Chelvarayan, Anushia; Fu Hao, Lim; Sook Fern, Yeo; Hashim, Hazlaili (RSF Conference Series: Business, Management and Social Sciences, 2025)
In recent years, changes in the commercial sector, along with the growing popularity of the Internet, have made Malaysian businesses increasingly conscious of the relevance of E-business in establishing a competitive advantage in the worldwide market. As a result, a greater knowledge of the elements that impact online purchase intent might aid in the development of more effective marketing strategies for certain segments. Four variables affecting online purchase intent were chosen for this study: trust, product and service quality, customer satisfaction, and delivery time. Three factors substantially affected online purchase intention, according to 203 Generation X respondents. The only exception was the quality of the product and service. Researchers, online platform developers, financial institutions, marketers, and the government would benefit greatly from the data and information gathered in this study since we will be able to assess and understand the variables that influence Gen X in Malaysia to purchase online.